Kitchenova Tech Enterprise - Mohamad Noorisham, Nur Ishabella; Mohd Nasir, Nur Aliah; Ahmad, Intan Balqis; Nazlie, Qistina Balqis; Yatim Bakhtiar, Muhammad Hazim (2025)
Kitchenova Tech Enterprise is a forward-thinking startup revolutionizing kitchen convenience with its innovative 3-in-1 ladle featuring a built-in thermometer, button-controlled water release, and standard soup scoop. Targeting modern home cooks and small food business owners aged 24–45, the company serves a market worth RM5.76 million with projected annual growth of 40–55% in the first three years. Focused on quality, functionality, and innovation, Kitchenova aims to become a leading Malaysian kitchenware brand and expand globally through continuous innovation and strategic marketing.